Model DL Berbantuan Media Menemukan Pola Kemampuan Berpikir Kreatif dan Curiosity dengan Gaya Kognitif - Rahmayani, Bulan; Junaedi, Iwan; Walid, Walid (Universitas Muria Kudus, 2023)
The purpose of this research is the achievement of student’s curiosity and creative thinking ability by DL using Mobile Learning Media, and the pattern of curiosity and creative thinking ability in terms of impulsive and reflective. This research applied a mixed method with a sequential exploratory model. The research used purposive sampling technique. The results are (1) A creative thinking ability and curiosity by DL model using Mobile Learning Media achieved minimal mastery; (2) the group of students with impulsive cognitive styles fulfilled the patterns of components of the creative thinking ability and the curiosity, i.e. (a) fluency, eksploration, and searching; (b) fluency, searching, and question; (c) fluency, novelty eksploration, and searching; and (d) fluency, novelty, eksplorastion, searching, and question; (3) the group of reflective cognitive style students fulfilled the components of a creative thinking ability and curiosity, i.e. (a) fluency, flexibility, eksploration, and searching; (b) fluency, flexibility, eksploration, searching, and question; (c) fluency, flexibility, novelty, eksploration, and searching; (d) fluency, flexibility, novelty, eksploration, searching, and question; (e) fluency, flexibility, novelty, eksploration, searching, and invention; (f) fluency, flexibility, novelty, eksploration, searching, question; and invention.